BILINGUALISM IN TEACHING MATHEMATICS TO YOUNG LEARNERS IN EFL SETTING - Kurniawati, Nia (Jurnal Vidya Karya, 2012)
This study tried to investigate the practice in teaching mathematics through English to young learners in EFL setting in a private elementary school in Cianjur. This study was conducted as an effort to find out the fact behind the practice of using English as instruction language at school especially at International Standard School. The findings revealed that in practice the concept of bilingual teaching was not done properly. The activity was dominantly in Indonesia while English was used only at the beginning to introduce the students to new mathematics terms in English. While the text book and exercise book are written in English, the test is in Indonesia. Most students considered it difficult to understand mathematics in English. However, from the questionnaires it was found that the students’ attitude toward their native and national language is not positive. Most of them see English as the most important and prestigious language. In contrary, Sundanese is considered less popular and the most difficult language for them